River terraces and alluvial fans: The case for an integrated Quaternary fluvial archive. (15th June 2017) - Mather, A.E.; Stokes, M.; Whitfield, E.
Abstract: The fluvial archive literature is dominated by research on river terraces with appropriate mention of adjacent environments such as lakes. Despite modern sedimentary basins comprising a significant (>88%) volume of distributive fluvial systems, of which alluvial fans (>1 km, <30 km in scale) are a significant part, interaction with these environments tends to be neglected and discussed in separate literature. This paper examines the dynamic role of alluvial fans within the fluvial landscape and their interaction with river systems, highlighting the potential value of alluvial fans to the wider fluvial archive community. Published literature is used to examine both thematic and geographical based benefits of alluvial fan research that can assist understanding of Quaternary fluvial archives. 3 regional case studies are presented that illustrate the interaction between alluvial fan and river terrace archives at Quaternary time-scales at 3 different stages of landscape evolution. These are i) continuous mountain front alluvial fans interacting with a non incising but laterally eroding axial fluvial system; ii) alluvial fans which transition into fluvial terraces as sedimentary basins shift from net aggradation to net incision and iii) tributary-junction alluvial fans that develop predominantly within incising river valley systems. A simple conceptual model is proposed to summarise the dynamic role of alluvial fans within this landscape context. The alluvial fans act as potential 'buffers' between hillslopes and river terrace records under 'top down' climate-driven high sediment supply and alluvial fan aggradation, and 'couplers' during periods of less sediment (in relation to water) discharge and alluvial fan incision. These dynamics will change with the addition of 'bottom up' controls such as main river incision, which will typically enhance the coupling effect of both systems. Highlights: Provides the first review paper linking alluvial fan research with research into fluvial archives. Pulls together material from across sub-disciplines. Fans act as important 'buffers' or 'couplers' within the fluvial landscape. Fan/river interactions change in response to top down and bottom up system drivers. Dynamic relationships described in a conceptual model of alluvial fan/river interactions.